Identification and injury to the inferior hypogastric plexus in nerve-sparing radical hysterectomy - Li, Lei (Sci Rep, 2019)
Waterjet dissection of the inferior hypogastric plexus (IHP) resulted in a more rapid return of normal urodynamics than blunt dissection (control group) in patients who received laparoscopic nerve-sparing radical hysterectomy (NSRH) in a randomized controlled study. However, the definite reasons for these results were unknown. This subgroup analysis compared the neural areas and impairment in the IHP uterine branches harvested during NSRH as an alternative to the IHP vesical branches between the waterjet and control groups. This study included samples from 30 eligible patients in each group of the trial NCT03020238. At least one specimen from each side of the IHP uterine branches was resected. The tissues were scanned, images were captured, and the neural component areas were calculated using the image segmentation method. Immunohistochemical staining was used to evaluate neural impairment. The control and waterjet groups had similar areas of whole tissues sent for evaluation. However, the control group had significantly fewer areas (median 272158 versus 200439 μm(2), p = 0.044) and a lower percentage (median 4.9% versus 3.0%, p = 0.011) of neural tissues. No significant changes in immunohistochemical staining were found between the two groups. For patients with residual urine ≤100 and >100 ml at 14 days after NSRH (42 and 18 patients, respectively), there were significantly different percentages of neural tissues in the resected samples (p < 0.001). Hence, Due to the accurate identification of IHP during NSRH, the waterjet dissection technique achieved better urodynamic results.